Case Studies of Severe Microfilaremia in Four Dogs Naturally Infected With Dirofilaria repens as the Primary Disease or a Disease Complicating Factor - Wysmołek, Magdalena E.; Klockiewicz, Maciej; Sobczak-Filipiak, Małgorzata; Długosz, Ewa; Wiśniewski, Marcin (Frontiers in Veterinary Science, 2020)
Subcutaneous dirofilariosis in dogs, caused by Dirofilaria repens, is an underdiagnosed disease, now recognized for its zoonotic potential, and growing distribution and prevalence across Europe and Asia. Our understanding of the pathogenicity in human and canine host remains unclear, but case reports suggest that microfilariae (Mf) as well as adult D. repens may directly cause internal organs damage or may be a factor complicating the course of other ailments. The purpose of the study was to report high Mf in dogs and to discuss potential relevance with co-morbidity. Our data from a modified Knott’s test performed on 62 infected dogs indicate that the median Mf count in D. repens infections is 675 Mf/ml and we consider microfilaremia above 10,000 Mf/ml as high intensity. This collection of case reports discusses 4 cases of high intensity D. repens microfilaremia in companion dogs; one presenting pathology from a very high intensity of adult D. repens with post-treatment complications, and 3 dogs in which high microfilaremia was detected incidentally during the management of other primary illnesses. To our knowledge this report describes the highest D. repens microfilaremia ever detected in a dog, at 178,000 Mf/ml. The issue of high microfilaremic infections in dogs is poorly studied and there is growing need to identify the presentation and understand the mechanisms of associated pathogenesis in the host-parasite relationship.